Where Does River Runoff Matter for Coastal Marine Conservation? - Fredston-Hermann, Alexa; Brown, Christopher J.; Albert, Simon; Klein, Carissa J.; Mangubhai, Sangeeta; Nelson, Joanna L.; Teneva, Lida; Wenger, Amelia; Gaines, Steven D.; Halpern, Benjamin S. (Frontiers in Marine Science, 2016)
Excess sediment and nutrient runoff from land-based human activities are considered serious threats to coastal and marine ecosystems by most conservation practitioners, resource managers, fishers, and other “downstream” resource users. Deleterious consequences of coastal runoff, including eutrophication and hypoxia, have been observed worldwide. Literature on integrated coastal management offers numerous methods to address land-based activities that generate runoff, but many of these approaches are time- and resource-intensive. Often, high-level conservation managers have few tools to aid in decisions about whether land-based threats that generate runoff are of sufficient concern to warrant further investment in planning and management interventions. To address this decision-making process, we present a decision tree that uses geophysical and ecological characteristics to sort any marine coastal ecosystem into a category of high, moderate, low, or minimal risk from the land-based threats of nutrient and sediment runoff. By identifying situations where runoff could influence biodiversity or ecosystem services, the decision tree assists managers in making informed, and standardized decisions about when and where to invest further efforts in integrated land-sea planning. We ground-truth the decision tree by evaluating it in five very different regions and conclude the tree classifies regions similarly to the existing literature that is available, but based on less information. Recognizing that the decision tree only encompasses environmental variables, we also discuss approaches for interpreting the decision tree's outputs in local social and economic contexts. The tree provides a tool for conservation managers to decide whether the scope of their work should include land-sea planning.